Analisis Kesulitan Membaca Pemahaman Teks Narasi pada Peserta Didik Kelas V SD - Oktarina Nur Restiani; Muh. Arafik; Titis Angga Rini; Oktarina Nur Restiani; Muh. Arafik (Universitas Negeri Malang, 2022)
Abstract: Difficulty in reading comprehension of narrative texts is the difficulty experienced by students in understanding the contents of narrative texts. The purpose of this study is to determine the fifth grade students' ability to read and understand narrative texts and the difficulties in reading comprehension of narrative texts experienced by fifth grade students at SDN Karangbesuki 1 Malang. The approach in this study uses descriptive qualitative by describing the phenomena encountered in the field and producing descriptive data. Data collection techniques are used in the form of observations, tests, and interviews. The results showed that the students' ability to read and understand narrative texts was low. In addition, it was also found that students had difficulties in determining who, when, and where aspects related to the level of literal understanding; difficulties in determining the main ideas and messages contained in reading texts on interpretive understanding; difficulties in concluding the contents of readings related to critical understanding; and difficulties in retelling the reading text using their own language at the level of creative understanding. Abstrak: Kesulitan membaca pemahaman teks narasi merupakan kesulitan yang dialami peserta didik dalam memahami isi teks narasi. Tujuan penelitian ini yaitu, untuk mengetahui kemampuan membaca pemahahaman teks narasi dan kesulitan membaca pemahaman teks narasi yang dialami oleh peserta didik kelas V SDN Karangbesuki 1 Malang. Pendekatan dalam penelitian ini menggunakan kualitatif deskriptif dengan mendeskripsikan fenomena yang ditemui di lapangan serta menghasilkan data deskriptif. Teknik pengumpulan data yang digunakan berupa observasi, tes, dan wawancara. Hasil penelitian menunjukkan kemampuan membaca pemahaman teks narasi yang dimiliki peserta didik tergolong rendah. Selain itu juga ditemukan bahwa peserta didik mengalami kesulitan dalam menentukan aspek siapa, kapan, dan dimana berkaitan dengan tingkat pemahaman literal, kesulitan menentukan gagasan pokok dan pesan yang terkandung dalam teks bacaan pada pemahaman interpretatif, kesulitan menyimpulkan isi bacaan berhubungan dengan pemahaman kritis, dan kesulitan menceritakan kembali teks bacaan menggunakan bahasa sendiri di tingkat pemahaman kreatif.